A retrospective study on drug utilization in patients with acute exacerbation of bronchial asthma in adults at tertiary teaching hospital in Bidar - D. B., Jyothi; Kulkarni, Gajanan P. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drug utilization plays a role in helping the health care system to understand, interpret and improve the drug use and continuous quality improvement. It plays an essential part of pharmaco Epidemiological studies. Methods: 100 prescriptions from patients with established diagnosis of acute exacerbation of Bronchial asthma were assessed from the Department of Pulmonary Medicine and the data gathered was analysed using MS Excel. Results: Majority of the prescriptions irrespective of severity received inhalation β2 agonist (formoterol) as a bronchodilator. Nebulization route was given for managing the acute exacerbations followed by inhalation route. Hydrocortisone was prescribed to all patients for managing acute Exacerbations. Montelukast was used an adjuvant therapy. Most of them were prescribed combination therapy. Theophylline was prescribed among all the methylxanthines. Conclusions: β2 agonists Combinations and corticosteroids are the most commonly prescribed combination drugs for asthma followed by methylxanthines. The most commonly prescribed asthmatic Medication in combination therapy was inhaled salbutamol with ipratropium followed by intravenous Hydrocortisone and oral Montelukast. The most commonly prescribed methylxanthine was intravenous Theophylline. Nebulization was preferred route to tackle the acute exacerbation of asthmatic symptoms.